2022
DOI: 10.12659/msm.937832
|View full text |Cite
|
Sign up to set email alerts
|

Application of Indocyanine Green Fluorescence Imaging Combined with Laparoscopic Ultrasound in Laparoscopic Microwave Ablation of Liver Cancer

Abstract: Background The aim of this study was to assess the effect of indocyanine green (ICG) fluorescence imaging combined with laparoscopic ultrasound in laparoscopic microwave ablation of liver cancer. Material/Methods This study retrospectively analyzed 61 patients who underwent laparoscopic microwave ablation of liver cancer, including laparoscopic microwave ablation with and without ICG fluoroscopy. Results The operative times, ablation times, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In recent studies, indocyanine green (ICG) fluorescence seems to be a valid tool to increase the safety of liver resection. Some authors [ 28 , 29 ] showed that LUS integrated with ICG fluorescence imaging permitted the identification of HCC nodules: in fact, the use of an LUS probe may be associated with difficulties in visualizing small subglissonean nodules which could be easily identified by ICG imaging. A single dose of ICG (generally 0.5 mg/kg) used for routine liver function tests (with the LiMON device) should be injected 24–36 h before the surgical procedure and it is sufficient to identify nodules using intraoperative fluorescence imaging.…”
Section: Icg Fluorescence Imagingmentioning
confidence: 99%
“…In recent studies, indocyanine green (ICG) fluorescence seems to be a valid tool to increase the safety of liver resection. Some authors [ 28 , 29 ] showed that LUS integrated with ICG fluorescence imaging permitted the identification of HCC nodules: in fact, the use of an LUS probe may be associated with difficulties in visualizing small subglissonean nodules which could be easily identified by ICG imaging. A single dose of ICG (generally 0.5 mg/kg) used for routine liver function tests (with the LiMON device) should be injected 24–36 h before the surgical procedure and it is sufficient to identify nodules using intraoperative fluorescence imaging.…”
Section: Icg Fluorescence Imagingmentioning
confidence: 99%
“…[8][9][10] However, this procedure often leads to hyperthermia-induced side effects on important organs adjacent to the lesion undergoing ablation. [11][12][13] Therefore, it is necessary to explore and develop novel treatment technologies to address these challenges.…”
Section: Introductionmentioning
confidence: 99%